Schizoglossum austromontanum, a novel new species from South Africa (Apocynaceae, Asclepiadoideae, Asclepiadeae) - Bester, Stoffel P.; Nicholas, Ashley (Phytotaxa, 2016)
A new species from southern Africa namely Schizoglossum austromontanum is described. Line-drawings, scans of the type material, images and a conservation assessment are provided.